Penguatan Karakter Religius dan Kesadaran Moral Siswa melalui Kajian Tahun Baru Islam di SMPN 2 Bangsal Mojokerto - Miftakhur Ridlo Ridlo (Journal of Science and Social Development, 2026)
Strengthening students’ religious character and moral awareness is an important need in facing the challenges of digital technology development and changes in adolescent behavior. This community service program aimed to improve students’ understanding of the meaning of the Islamic New Year as a momentum for hijrah and to instill religious values that can be applied in daily life. The activity was conducted at SMPN 2 Bangsal Mojokerto, targeting students in Grades VII, VIII, and IX as part of the commemoration of the Islamic New Year 1448 AH. The implementation method used an educational-participatory approach through preparation, implementation, and evaluation stages. The implementation stage consisted of interactive lectures, discussions, question-and-answer sessions, and reflections on the values of hijrah as they relate to students’ experiences. The results showed that students were able to understand hijrah not only as a historical event, but also as a process of self-transformation toward better behavior. Students were also able to identify character values such as honesty, discipline, responsibility, social care, respect, and self-control. This activity indicates that the study of the Islamic New Year can serve as an effective educational medium for strengthening students’ religious character and moral awareness in a contextual, reflective, and sustainable manner. These findings support the importance of collaboration between schools and higher education institutions in developing a religious culture that is relevant to the current needs of students in the school environment.